Within and among-genetic variation in Asian flax Linum austriacum (Linaceae) in response to latitude changes: Cytogenetic and molecular analyses - ZAHRA NOORMOHAMMADI; TINA SHAFAF; FATEMEH FARAHANI; MASOUD SHEIDAI; SEYED MEHDI TALEBI; YEGANEH HASHEMINEJAD-AHANGARANI FARAHANI (Society for Indonesian Biodiversity, 2015)
Noormohammadi Z, Shafaf T, Farahani F, Sheidai, Talebi SM, Hasheminejad-Ahangarani-Farahani Y. 2015. Within and among-genetic variation in Asian flax Linum austriacum (Linaceae) in response to latitude changes: Cytogenetic and molecular analyses. Biodiversitas 16: 145-150. Linum austriacum L. (Linaceae) which is known as Asian flax is an herbaceous medicinal plantspecies that grow in Iran in different latitudes and forms some local populations particularly in the West and North-West of the country.Within-and between-genetic diversity in response to altitude changes was investigated in geographical populations of L. austriacum byusing cytogenetic and ISSR molecular markers. These populations were diploid with 2n = 18 and differed significantly (P<0.05) in theirmean chiasma frequency and chromosome pairing. Significant positive correlation (r >0.90, P < 0.05) occurred between latitude and themean number of quadrivalents. The highest level of genetic diversity parameters as Shanon Information Index and gene diversityoccurred in Salavat-abad population. Moreover, the STRUCTURE analysis also identified this population as the most varied population.This population had medium altitude distribution. Mantel test performed between genetic distance and geographical distance showed nosignificant correlation (R2 = 0.09, p = 0.39). Pearson coefficient of correlation determined between genetic diversity parameters andaltitude, produced a significant negative correlation (r =-0.85, P<0.01) with the number of effective alleles. The present study revealedthat Linum austriacum populations do have some cytogenetic and molecular variation in response to altitude.